Encounters with Ultimacy?: Autobiographical and Critical Perspectives in the Academic Study of Religion - Hedges, Paul (Open theology, 2018)
"Ultimacy," it is argued, is not an area that academic studies in theology nor the study of religion can properly investigate; nevertheless, it is also illegitimate to argue therefore that claims to it are simply linguistic power plays. Using an autobiographical methodology, the author explores how their own "imagined" "mystical" experience and scholarly studies may shed light on approaching the study of religious experience, noting particularly work by Rudolf Otto, Robert Sharf, Gregory Shushan, and Ann Taves. Reflections are offered on studying religious experience, approaching ultimacy, and the relationship of theological and religious studies. Moreover, some critical and decolonial perspectives are brought to bear both on the author’s own work, academic studies, and contemporary debates around studying what may be termed "mysticism" or religious experience. The author also argues that the autobiographical and reflexive model offered herein may be a useful perspective for scholarship in the study of religion.